2016
DOI: 10.1016/j.physbeh.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of experimentally manipulated social status on acute eating behavior: A randomized, crossover pilot study

Abstract: Both subjective and objectively measured social status has been associated with multiple health outcomes, including weight status, but the mechanism for this relationship remains unclear. Experimental studies may help identify the causal mechanisms underlying low social standing as a pathway for obesity. Our objective was to investigate the effects of experimentally manipulated social status on ad libitum acute dietary intakes and stress-related outcomes as potential mechanisms relating social status and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 40 publications
5
77
1
1
Order By: Relevance
“…Cross-sectional investigations and metaanalysis on the relationship between subjective socioeconomic status and health outcomes have suggested that individuals who report lower levels of subjective socioeconomic status and rank are more likely to be at risk for weight gain, adiposity, diabetes, and overweight/obesity even when controlling for objective indicators of socioeconomic status (11)(12)(13)(14). One pilot feasibility study using a small sample has implied that people placed into disadvantaged social roles subsequently consume more calories, but under circumstances where those in disadvantaged roles are exposed to greater stress and potential aggression from those in dominant roles (15). However, no studies to date have experimentally tested whether the mere psychological experience of low subjective socioeconomic status actually stimulates appetite and caloric intake independent of other risk factors associated with low SES (e.g., low economic/material resources, heightened stress).…”
mentioning
confidence: 99%
“…Cross-sectional investigations and metaanalysis on the relationship between subjective socioeconomic status and health outcomes have suggested that individuals who report lower levels of subjective socioeconomic status and rank are more likely to be at risk for weight gain, adiposity, diabetes, and overweight/obesity even when controlling for objective indicators of socioeconomic status (11)(12)(13)(14). One pilot feasibility study using a small sample has implied that people placed into disadvantaged social roles subsequently consume more calories, but under circumstances where those in disadvantaged roles are exposed to greater stress and potential aggression from those in dominant roles (15). However, no studies to date have experimentally tested whether the mere psychological experience of low subjective socioeconomic status actually stimulates appetite and caloric intake independent of other risk factors associated with low SES (e.g., low economic/material resources, heightened stress).…”
mentioning
confidence: 99%
“…Again, this is distinct from mentioning the negative mental health impacts of climate change. In discussions of education and behavior, there is no mention of educating the affluent to understand what it 'feels' like to be in poverty [208][209][210]; this is an upstream step that might incentivize policy makers to more viscerally understand how neoliberal 'behaviors' influence the status quo. Moreover, the term living wage (or even the word 'wage' makes no appearance)-which seems odd given its connection to positive mental health and the healthy behaviors, (including healthy dietary patterns and opportunity for recreation) which planetary health is attempting to promote [211][212][213][214][215][216][217][218].…”
Section: Academic Planetary Health Expanding the Discoursementioning
confidence: 99%
“…Research on allostatic load informs us that past experiences in the ecological theatre would prime the individual for higher levels of inflammation and oxidative stress in response to stress. Consider that even the mere researcher-invoked feeling of poverty or belonging to an SES "out-group" (in a laboratory setting) is enough to alter dietary choices in the direction of low-nutrient, high-calorie foods [93][94][95].…”
Section: Dysbiosis and The Mental Environmentmentioning
confidence: 99%